National economic impacts of an EU environmental policy: an applied general equilibrium analysis - Klaus Conrad; Tobias F. N. Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
The objective of this paper is to quantify the economic effects of the introduction of a system of tradable permits in the European Union (EU). For this purpose we use linked applied general equilibrium models (AGE) for eleven EU member countries. This method enables us to measure the change in competitiveness for domestic industries, the impact on growth, employment and inflation in member countries, and the cost and benefits of a cooperative approach to adhere to a EU target of emissions of air pollutants. The results we will present are first results from the SOLVGE/GEM-E3 Projekt. GEM-E3 stands for General Equilibrium Modeling for Energy - Economy - Environment, a joint undertaking of NTUA-Athens (P. Capros, P. Georgakopoulos), CESKULeuven (S. Proost and D. Van Regemorter), Univ. Mannheim and ZEW (K. Conrad and T. Schmidt), GEMME-CEA (N. Ladoux), Univ. Strathclyde (P. MacGregor), CORE-UCL (Y. Smeers), With respect to a policy on greenhouse gases we will quantify the economic impact for the, EU by introducing a EU-wide tradable permit system, free of charge and based on the present energy intensity and energy mix. Under growth there will be a positive market price for permits with demand by countries where the cost of substitution are high and supply by those countries where the cost of substitution are low. We will measure economic performance and trade flows under a noncoordinated CO2 policy where each country limits the emission of CO2 by 10% and will compare the result with a cooperative outcome where the European Union as a decision maker aims at reducing CO2 by 10%.
Keywords: 330